Degradation and orientation of collagen / Saiful Bahri Mohd Yasin - Mohd Yasin, Saiful Bahri (2008)
The degradation of collagen properties such as UV light exposure, solvent effect and pH affect was investigated. At initially, Difference Scanning Calorimetric (DSC) was used to investigate the temperature profile of raw collagen. Then, collagen was diluted in water, a mild acetic acid and hydrochloric acid to form collagen film by bulk film into petri dish and thin film on glass slide as well as Polytetrafluorethylene (PTFE) coated glass slide. The film was exposed to Ultraviolet light to investigate the degradation of the molecular structure by using Fourier Transform Infrared Spectrometer (FTIR) spectrum. The Polarized Microscope (PLM) was utilized to observe the orientation of the collagen on glass and Polytetrafluorethylene (PTFE) coated glass slide. The finding for these studies was employed for application of thin film used for medical purposes.